2018
DOI: 10.1371/journal.pone.0205928
|View full text |Cite|
|
Sign up to set email alerts
|

Aerosol prime-boost vaccination provides strong protection in outbred rabbits against virulent type A Francisella tularensis

Abstract: Tularemia, also known as rabbit fever, is a severe zoonotic disease in humans caused by the gram-negative bacterium Francisella tularensis (Ft). While there have been a number of attempts to develop a vaccine for Ft, few candidates have advanced beyond experiments in inbred mice. We report here that a prime-boost strategy with aerosol delivery of recombinant live attenuated candidate Ft S4ΔaroD offers significant protection (83% survival) in an outbred animal model, New Zealand White rabbits, against aerosol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 57 publications
(60 reference statements)
4
12
0
Order By: Relevance
“…These data suggest that BHI-grown SCHU S4 is a more rigorous challenge for demonstrating protection in vaccine studies than MHB-grown SCHU S4. Considering that we have previously shown that attenuated derivatives of SCHU S4 outperform LVS and protect rabbits well against both morbidity and mortality at even higher challenge doses of SCHU S4 grown in BHI, this further illustrates the superior performance of these attenuated derivatives as potential vaccine candidates (46). The survival of LVS-vaccinated rabbits and consistent/higher SF from the aerosol characterization studies both argue that BHI should be used in pivotal Ft efficacy studies to achieve a rigorous, reproducible aerosol challenge sufficient to demonstrate the efficacy of potential vaccine candidates in animals.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…These data suggest that BHI-grown SCHU S4 is a more rigorous challenge for demonstrating protection in vaccine studies than MHB-grown SCHU S4. Considering that we have previously shown that attenuated derivatives of SCHU S4 outperform LVS and protect rabbits well against both morbidity and mortality at even higher challenge doses of SCHU S4 grown in BHI, this further illustrates the superior performance of these attenuated derivatives as potential vaccine candidates (46). The survival of LVS-vaccinated rabbits and consistent/higher SF from the aerosol characterization studies both argue that BHI should be used in pivotal Ft efficacy studies to achieve a rigorous, reproducible aerosol challenge sufficient to demonstrate the efficacy of potential vaccine candidates in animals.…”
Section: Discussionsupporting
confidence: 58%
“…When rabbit minute volume was plotted by aerosol exposure days, there was day-to-day variation as shown in Figure 5B and these differences were significant by one-way ANOVA using Brown-Forsythe’s test ( p <0.0001). In the midst of these studies, we had also evaluated inhalation of small particle aerosols containing attenuated strains as a potential means of delivery for live vaccines (4). Using the data acquired during those studies, we evaluated whether repeated aerosol exposures of rabbits in the nose-only tubes would alter respiratory function (Supplemental Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cause of death in the rabbits appeared to be severe septic shock and/or acute respiratory distress syndrome. Additionally, we have shown that attenuated strains of F. tularensis can protect rabbits against aerosol challenge with virulent SCHU S4 (4)(5)(6). The degree of protection against morbidity and mortality is a function of the attenuated strain used, the number of vaccinations, and the route of vaccination.…”
mentioning
confidence: 99%